2007
DOI: 10.1016/s1441-3582(07)70041-1
|View full text |Cite
|
Sign up to set email alerts
|

Question Stability in Brand Image Measurement: Comparing Alternative Answer Formats and Accounting for Heterogeneity in Descriptive Models

Abstract: This article originally published as Dolnicar, S and Grun, B, Question stability in brand image measurement: Comparing alternative answer formats and accounting for heterogeneity in descriptive models, Australasian Marketing Journal, 15(2), 2007, 26-41. Question stability in brand image measurement -Comparing alternative answer formats and accounting for heterogeneity in descriptive models. AbstractHigh quality image data on how consumers perceive brands is essential to make good brand management decisions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…More specifically, the performance of six different methods of measuring destination image which can be used in survey studies is compared using three key criteria of data quality: concurrent validity, survey completion time, and stability (or test-retest reliability). Prior work only investigated stability in the examination of a range of different answer formats (Dolnicar & Grün, 2007). Dolnicar, Grün and Leisch (2011) used similar criteria but only compared two different answer formats.…”
Section: Introductionmentioning
confidence: 99%
“…More specifically, the performance of six different methods of measuring destination image which can be used in survey studies is compared using three key criteria of data quality: concurrent validity, survey completion time, and stability (or test-retest reliability). Prior work only investigated stability in the examination of a range of different answer formats (Dolnicar & Grün, 2007). Dolnicar, Grün and Leisch (2011) used similar criteria but only compared two different answer formats.…”
Section: Introductionmentioning
confidence: 99%
“…While some authors have defended the use of the former (Gardner & Levy, 1955;Durgee & Stuart, 1987;Danes, Hess, Story, & Vorst, 2012), others have opted for the latter, and the majority of authors have suggested the use of mixed techniques for image studies, combining qualitative and quantitative tools during the different study phases (Churchill, 1979;Zaichkowsky, 1985;Sanz de la Tajada, 1994;Low & Lamb, 2000;Del Rio, Vazquez, & Iglesias, 2001;Martinez & De Chernatony, 2004;Dolnicar & Grün, 2007;Koubaa, 2008;Park, 2009;Huang, 2010); (2) Although there are scales that allow for the measurement of partial dimensions of brand image, there is yet to be an agreement on a standard set of attributes; that is, items to be included in a scale for measuring the overall image of any type of brand, regardless of the specific brand product category; (3) Dobni and Zinkhan (1990) summed up the process that is typically followed when studying brand image using combined qualitative and quantitative instruments. Once again, the lack of agreement as to a specific technique and measurement scale is evident.…”
Section: Literature Review Brand Imagementioning
confidence: 99%
“…Two studies have hypothesized possible effects of answer formats on results derived from brand image studies: Dolnicar, Grün and Leisch (2011) compared a forced-choice binary format with a multi-category format concluding that results from the brand image study using the binary format were the same in terms of managerial interpretation and were equally reliable, but saved respondents' time in completing the questionnaire and were perceived by respondents as simpler, thus representing a valid and user-friendly measure for brand image measurement. Dolnicar and Grün (2007) used only the criterion of stability to compare answer formats for brand image measurement and concluded that the forced-choice binary measure produced the most stable answers.…”
Section: Factors Hypothesized To Affect Brand-attribute Association Smentioning
confidence: 99%